Growing differently: A structural classification for European NUTS-3 regions - Jan Weber; Jan Schulz (The University of Utah, Department of Economics, 2022)
We document two novel stylized facts on European integration and cohesion. First, we show that the interregional income distribution, measured as GDP per capita at the NUTS-3 level, is bimodal for all considered years. Second, we demonstrate that this mixture of two log-normal distributions provides an excellent fit for this interregional distribution in all considered years. We put forward two meso-level interpretations of these stylized facts, based on heterodox growth theory: The log-normality of the individual clusters hints at a stochastically multiplicative process, where growth is strongly path-dependent. This can be derived from maximum entropy considerations. However, the bimodality in the income distributions also implies two separate growth mechanisms. We show that the high-variance log-normal distribution governs the dy- namics at both tails of the income distribution, which might be interpreted as the core and periphery and the low-variance variant the bulk of the distribution, thus inter- pretable as a semi-periphery.
Keywords: C46; D63; F15; F43; C14; C63; 330; Inequality; Europe; Maximum Entropy; Geometric Brownian Motion; Core; Periphery; Resilience